Vulnerability of the Health Sector to Climate Change. The Case of Dengue - Retana, José Alberto (2008)
The vulnerability of health sector in Costa Rica was characterized by its exposition, sensibility and resilience components. The dengue disease was taken as a study case. Was found a relationship between ENOS phases and dengue cases. The future vulnerability was estimate using this relationship, the actual vulnerability study and the climate schenarios modelling, Those actual risk areas, would be more vulnerabities if temperature increases in the future as a result of climate change.